Proposta de um modelo para o desenvolvimento de competências dos estudantes de engenharia - Garbin, Fernanda Gobbi De Boer (2022)
Due to society’s current demands, new National Curricular Guidelines for Engineering course programs were published in 2019, highlighting the need for active teaching methodologies and technology for the development of the students’ competences. The rising interest regarding teaching methods for developing competences can be observed in national and international studies, alongside the need for research on the integration between such methodologies and digital technology. Considering this, we aim to answer the following question: how can we promote teaching for the developing of competences in an Engineering course program? As a solution, we attain our general objective by proposing one such teaching program model. Our specific objectives: (i) to identify the content, methodologies, and technologies to answer this specific need in Engineering programs; (ii) to create a learning experience geared towards the development of competences that is adequate to the context of application; (iii) to evaluate the performance of our proposed model in relation to said development. We based ourselves on the Technological Pedagogical Content Knowledge (TPACK) model, which elaborates on the influence of teaching methodologies, technology, and contents for the development of competences. The proposed model was applied in the Production Engineering program of the Federal University of Pampa (UNIPAMPA), more specifically to the Simulation curricular module. As to the classification of this research, it is of the applied category, with exploratory objectives and mixed methodologies. The research method chosen was the Design Based Research (DBR), and we incorporated its qualitative and quantitative aspects. As a result, the proposed model has a three-phase structure of planning, implementation, and reflection, and it is adequate to the project of a learning experience that promotes the development of competences, according to our analysis of student interviews and evaluations. This research brings theoretical and practical contribution in the studying of the development of competences, not only because of the need for implementation of the new curricular guidelines in Engineering programs in order to adhere to the criteria for the national qualification of engineers, but also to generate learning more significant and engaging learning environments.